Intelligent Financial Portfolio Composition based on Evolutionary Computation Strategies - Gorgulho, Antonio; Neves, Rui F.M.F.; Horta, Nuno C.G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The management of financial portfolios or funds constitutes a widely known problematic in financial markets which normally requires a rigorous analysis in order to select the most profitable assets. This subject is becoming popular among computer scientists which try to adapt known Intelligent Computation techniques to the market$1 (Bs domain. This book proposes a potential system based on Genetic Algorithms, which aims to manage a financial portfolio by using technical analysis indicators. The results are promising since the approach clearly outperforms the remaining approaches during the recent market crash.s
Preface -- Introduction -- Related Work -- Solution$1 (Bs Architecture -- System Validation -- Conclusions and Future Work -- References -- Appendixes.s
Keywords: Engineering; Artificial intelligence; Finance; Engineering; Computational Intelligence; Financial Economics; Artificial Intelligence (incl. Robotics).